1999
DOI: 10.1143/jjap.38.6219
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Beam Epitaxial Growth of InAs Quantum Dots Directly on Silicon

Abstract: InAs quantum dots (QD) embedded in a silicon matrix show a photoluminescence line at a wavelength of about 1.3 µm [Semicond. Sci. Technol. 13 (1998) 1262]. This wavelength range is very interesting for the integration of classical silicon technology with optical fiber applications for chip-to-chip or intra-chip communication. To get InAs QDs of reproducible size and shape the growth conditions for the formation of quantum dots have to be optimized. Here, we report on detailed investigations on the molecular be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…(001) substrates were hydrogenpassivated, details on their preparation and optimized growth conditions can be found in [9,10]. (001) substrates were hydrogenpassivated, details on their preparation and optimized growth conditions can be found in [9,10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(001) substrates were hydrogenpassivated, details on their preparation and optimized growth conditions can be found in [9,10]. (001) substrates were hydrogenpassivated, details on their preparation and optimized growth conditions can be found in [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…In a former study on the embedding of QDs in a silicon matrix we reported on the possibility of growing up to 10 11 cm --2 InAs QDs and the formation of large indium clusters between the InAs QDs [9]. Further, we investigated the QD size distribution, ways of improving their uniformity as well as the defect structure in the QDs, information which is essential for a later application of this system [10].…”
mentioning
confidence: 99%
“…Secondly, arsenic (As) beam equivalent pressure (BEP) dependence of dot formation was studied throughout the entire pressure range from 9.2 Â 10 À6 to 1.2 Â 10 À7 Torr. This subject was studied by Hansen et al, who observed that a small As/In ratio is crucial for obtaining high dot density [7]. The reason of this is still not very clear.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in InAs quantum dots has been extended to those fabricated on Si substrates because of the potential application in Si-based optoelectronic devices [6][7][8]. From the standpoint of materials physics, InAs quantum dots on Si represents a substantially more complex subject.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to InAs quantum dots on GaAs (001), InAs/ Si(001) is associated with a much higher lattice mismatch (11%) as well as a polar-nonpolar interface. Currently, the understanding of the formation mechanism of InAs quantum dots on Si is lacking [7,9,10]. There is very little knowledge in the literature with regard to controlling the dot size distribution and density, two important concerns for optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%